Relationship Between CHA2DS2-VASc Score and Right Ventricular Dysfunction in Patients With Acute Pulmonary Thromboembolism - Gok, Murat; Kurtul, Alparslan; Harman, Murat; Kara, Meryem; Suleymanoglu, Muhammed; Ornek, Ender (Sage Publications Inc, 2018)
In this study, the association between the right ventricular dysfunction (RVD) and CHA2DS2-VASc (C: congestive heart failure or left ventricular systolic dysfunction, H: hypertension, A: age of >= 75 years, D: diabetes mellitus, S: previous stroke, V: vascular disease, A: age between 65 and 74 years, Sc: female gender) scores was investigated in patients with acute pulmonary thromboembolism (PTE). The patients have been assigned to 3 subgroups as massive, submassive, and nonmassive PTE. The CHA2DS2-VASc scores were calculated for all of the patients, and the scores have been classified into 3 groups as the scores between 0 and 1, the scores of 2, and the scores of 3 and over. The independent predictors of the RVD were investigated by the univariate and multivariate regression analyses. The independent predictors of the RVD were determined to be the CHA2DS2-VASc scores (P = .034), the systolic pulmonary artery pressure (P < .001), the presence of acute deep vein thrombosis (P = .007), high simplified Pulmonary Embolism Severity Index (P < .001), D-dimer (P < .006), and the mean platelet volume (P < .001). The CHA2DS2-VASc scores predicted the RVD with 70% sensitivity and 50% specificity as determined by the receiver operating characteristic analysis. The CHA2DS2-VASc score is an independent predictor of the RVD in patients with acute PTE.
Keywords: CHA2DS2-VASc score; pulmonary thromboembolism; right ventricular dysfunction